ATP-citrate lyase links cellular metabolism to histone acetylation - Wellen, Kathryn E. (2009)
Histone acetylation in single cell eukaryotes relies on acetyl-CoA synthetase enzymes that utilize acetate to produce acetyl-CoA. Metazoans, however, use glucose as their main carbon source and have exposure to only low concentrations of extracellular acetate. We show that histone acetylation in mammalian cells is dependent on ATP-citrate lyase (ACL), the enzyme that converts glucose-derived citrate into acetyl-CoA. We find that ACL is required for increases in histone acetylation in response to growth factor stimulation and during differentiation, and that glucose availability can impact histone acetylation in an ACL-dependent manner. Together, these findings suggest that ACL activity is required to link growth-factor-induced increases in nutrient metabolism to the regulation of histone acetylation and gene expression.